The Influence of Financial Distress, Audit Committee, Audit Quality, and Leverage on Voluntary Disclosure: A Study on Infrastructure Sector Companies Listed on the Indonesia Stock Exchange from 2020 to 2023 - M. Rizal Dika Putra; Afrizal; Wiwik Tiswiyanti (Jurnal Multidisiplin Madani, 2024)
The purpose of this study is to explain the independent variables, namely financial distress, audit committee, audit quality, and leverage, to analyze their influence on the dependent variable, namely voluntary disclosure. The data analysis method in this study uses the regression analysis method, whose calculations use SPSS version 26. This study uses multiple linear regression because the independent variables used are more than one variable. The multiple regression analysis method used in this study includes descriptive statistics, classical assumption tests, hypothesis testing, and statistical tests. From the simultaneous test results, an F value of 19.455 is obtained, which is positive, and the significance test result of 0.000 is smaller than 0.05. Thus, financial distress, audit committee, audit quality, and leverage simultaneously affect voluntary disclosure. From the partial test obtained, the four independent variables, namely financial distress, audit committee, audit quality, and leverage, partially have an influence on voluntary disclosure.